Decoding vascular aging: implications for atherosclerosis progression and clinical intervention - Silumbwe Ceaser Wankumbu; Xiao-Man Ji; Ming Xu (Exploration of Drug Science)
Age-related pathologies, particularly cardiovascular disorders, pose a significant global health concern. The World Health Organization (WHO) predicts an increase in advanced mortality by 2030 unless critical interventions are implemented. Atherosclerosis remains the major cause of various cardiovascular diseases. Hence, this review focused on the interaction between known mechanisms of vascular aging, disease manifestation, and progression during atherosclerosis. In the review, we highlighted five altered vascular mechanisms in cardiovascular models: genomic instability, neurohormonal deregulation, epigenetics, protein regulation, and the gut microbiome. The articles were selected from various indexed scientific databases. It is important to note that the mechanisms are equally interrelated with other aging pathways, such as inflammation and senescence. In conclusion, atherosclerosis is multifaceted and cholesterol-lowering therapy has been widely used. However, more than one specific action line is required to eradicate or slow down its manifestation. Equally, establishing a balance between aging stressors resulting in vascular injuries and stress buffering mechanisms during aging is critical to the treatment of atherosclerosis. The promising therapeutic targets reviewed include the angiotensin (1–7)/MAS axis, the gut microbiome, histone deacetylases, DNA repair systems, noncoding RNAs, β3/dopamine adrenoceptors, senescence and inflammation checkpoints.